Stressors, stress level and its relation to the clinical performance of University of the Philippines College of Dentistry Clinicians SY '07-'08 - Bartolome, Marjorie; Dacuyan, Will P.; Yumul, Giselle S. (Adviser).
The study aimed to correlate stressors and stress level with the clinical performance among students of University of the Philippines College of Dentistry (UPCD). Questionnaires containing 5 groups of stressors categorized into academic/clinical requirements, family, interpersonal and faculty/administration factors were formulated based on previous studies that identified stressors of dental students. These were distributed to 50 clinicians of the UPCD. Clinical grades of the participating clinicians were provided by the Office of the College Secretary. Obtained data were processed using descriptive statistics and the Pearson's Correlation with a p-value of 0.05. Norms were developed using the whole clinician population as the bare sample yielding a mean value of 2.32 with standard deviation value of 0.45. To determine the correlation of average stress score and average clinical grade, a 95% level of significance was used. Results revealed that the stressors students found most stressful in their whole years of stay in the college are finals week, 3rd year 1st semester subjects, failing in subjects and being delayed, difficult exams, voluminous work, practical exams, clinical works which included patient factors, among others. Results showed that most of the students experience a moderate level of stress, regardless of change in their grades from laboratory to clinical subjects. Since the computed p-value is 0.6059 which is > than 0.05, then we do not reject null hypothesis. Based on the statistical analysis done, the Average Clinical Grade for all subjects is not affected by the increase or decrease of the Average Stress that the students are experiencing. Therefore, stressors and stress level of UPCD clinical students has no significant relationship on their clinical grades.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Stress; Dental students -- University of the Philippines